It is: 5+(3*7) = 26
3x7 = 21
y = -1/(3x7 + 2x - 9)y = -(3x7 + 2x - 9)-1y' = -(-1)(3x7 + 2x - 9)-2(3x7 + 2x - 9)'y' = (3x7 + 2x - 9)-2(21x6 + 2)y' = (21x6 + 2)/(3x7 + 2x - 9)2
We don't know and can't calculate it, until we're given the value of 'x'.
To find 6x7 using 3x7, you can simply double the result of 3x7. This is because multiplication is distributive over addition, meaning that multiplying a number by a sum is the same as multiplying the number by each addend and then adding the products. In this case, 6x7 can be thought of as (3+3)x7, which equals 3x7 + 3x7, or 21 + 21, which equals 42.
3x7
3(7 + 2) = 3x7 + 3x2 is an example of the distributive law.The distributive law connects multiplication and addition.
2x7 = 14 x7 = 7 3x7 = 3*7 = 21
21
-21
133
41